219k views
4 votes
If (m-1/m) = 3, find the value of m³-1/m³​

1 Answer

4 votes

⇒The trick here is to find the value of m first using the equation given.


(m-1)/(m) =3\\m-1=m(3)\\m-1=3m\\m-3m=1\\-2m=1\\(-2m)/(-2)=(1)/(-2) \\m=-(1)/(2)

Note I used cross multiplication to solve for m

Now to find what
(m^(3) -1)/(m^(3) ) substitute the value of m in the expression and simplify.


=((-(1)/(2)) ^(3) -1)/((-(1)/(2) )^(3) ) \\\\=(-(1)/(8)-1 )/(-(1)/(8) ) \\=(-(9)/(8) )/(-(1)/(8) ) \\=9

⇒The value is 9

Goodluck!!

User Andreas Vogl
by
5.7k points